Chai: More than just Tea! - Manji, Aabid (2008)

(untitled)
This paper seeks to apply a traditionally lacking critical approach to the corruption and social capital literatures investigating the dialectical relationships therein through the eyes of Kenyan entrepreneurs. It is envisaged that significant insight is missed out on in the traditional approaches to the concept of corruption through its treatment as merely an economic problem, rather than a socially complex phenomenon. Therein, this paper draws from the social capital literature and the corruption literature to investigate and give credence to contextually constructed knowledge.